The acquisition of English grammar among bilingual Malay- English primary school children - Mohamed Salleh, Rabiah Tul Adawiyah; Di Biase, Bruno; Ramlan, Wan Nur Madiha (2020)
This paper presents the acquisition of English grammar among 7 Malay-English bilingual primary school children. Studies to document the English acquisitional trajectory of Malaysian learners are scant and this normative data is imperative for syllabus-designers, policy-makers, teachers as well as linguists to understand the root cause of the students’ low proficiency in English. In this study, the children, aged 9 years old, have attended the same primary school which employed the national KSSR syllabus for 2 years (since 7 years old). Other than the school domain, the children’s home language factor was also examined. The speech output of the children was elicited from an individual English recording session where each child was asked to narrate a wordless storybook and describe the differences between two pictures. Their English grammatical acquisition was then analysed using the Processability Theory framework. The results indicate that other than the home language environmental factor, the children’s language aptitude also contributes to their English grammatical acquisition. In terms of PT’s developmental stages, it was also found that the children’s English morphological development adheres to the stages predicted by PT. The findings also lend credence to PT’s typological applicability across different populations.